Clustering multiple robots with serialisation. (1st January 2014) - Kambayashi, Yasushi; Satta, Keisuke; Shibata, Ko; Sugiyama, Shota; Takimoto, Munehiro; Yamachi, Hidemi
This paper presents the design of an intelligent cart system to be used in a typical airport. The system consists of a set of mobile software agents to control the cart and provides a novel method for alignment. To avoid excessive energy consumption through the collection of the carts, we have used ant colony optimisation that uses the vector values of the scattered carts in the field. Waiting time and route to the destination of each cart is computed based on the cluster to be created. These routes and waiting times are conveyed by the mobile software agent to each cart, causing the group to form into rough lines. Because the carts are clustered by the similarity of their vectors, we have observed that several groups have appeared to have been successfully aligned by this method. We also propose a line forming technique for intelligent carts to actually align themselves.